An embodied belonging: Amenorrhea and anorexic subjectivities (Medicine Anthropology Theory, 2014)
Until the publication of the DSM-V in 2013, amenorrhea was one of the four criteria that comprised anorexia nervosa. Diagnostically, amenorrhea played a definitional role, dividing the ‘strictly’ anorexic from their ‘subthreshold’, menstruating peers; however, the implications that menstrual cessation, and menstruation itself, held for the lived realities and identities of women with anorexia remain under-explored. In this article, I examine the positioning of menstruation and amenorrhea in the narratives of Israeli women diagnosed with eating disorders during the eras of the DSM-IV and DSM-IV-TR. I find that the participants’ narrative uses of amenorrhea mirrored, and at times explicitly engaged with, the official diagnosis of anorexia nervosa. Notably, although the participants invoked amenorrhea as a defining sign of illness, they did not cast menstruation as a sign of health rather, they spoke of their menstrual periods as contradicting their anorexic-identified selves. Amenorrhea, then, emerged as central in the embodied making of anorexic subjectivities.